2021
DOI: 10.3389/fphar.2021.755569
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology for Targeted Therapy of Atherosclerosis

Abstract: Atherosclerosis is the major cause of heart attack and stroke that are the leading causes of death in the world. Nanomedicine is a powerful tool that can be engineered to target atherosclerotic plaques for therapeutic and diagnosis purposes. In this review, advances in designing nanoparticles with therapeutic effects on atherosclerotic plaques known as atheroprotective nanomedicine have been summarized to stimulate further development and future translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…The outcome of coronary heart disease leads to a disruption of the extracellular matrix during the inflammatory and reparative phase [ 60 ]. Nanoparticles, loaded with pitavastatin, are able to protect the extracellular matrix from postischemic remodeling, by blocking the migration of monocytes [ 61 , 62 ]. This confirms that the targeted statins can improve the healing process of the heart area affected by ischemia [ 63 , 64 ].…”
Section: Biological and Clinical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of coronary heart disease leads to a disruption of the extracellular matrix during the inflammatory and reparative phase [ 60 ]. Nanoparticles, loaded with pitavastatin, are able to protect the extracellular matrix from postischemic remodeling, by blocking the migration of monocytes [ 61 , 62 ]. This confirms that the targeted statins can improve the healing process of the heart area affected by ischemia [ 63 , 64 ].…”
Section: Biological and Clinical Effectsmentioning
confidence: 99%
“…PLGA seems particularly suitable thanks to its easy degradation, its prolonged release of the drug, and its very high biocompatibility [ 65 ]. Hence, the pitavastatin–PLGA complex has been proposed as a therapeutic strategy for postischemic remodeling of the left ventricle in the case of CAD [ 61 , 62 , 63 , 64 , 65 , 66 ] ( Table 4 ). Other studies have reported atorvastatin-induced improvement in left ventricular remodeling after acute myocardial infarction, through the interaction with collagen metabolism, such as with matrix metalloproteinases [ 67 , 68 ].…”
Section: Biological and Clinical Effectsmentioning
confidence: 99%
“…Given these considerations, one of the most important targets in neuro-regenerative approaches after ischemia is the penumbra region. The duration of occlusion determines the severity of damage and the prognosis of the patients [ 100 ]. The number of surviving neurons after a stroke defines cerebral functional deficits.…”
Section: Mtor After Cerebral Ischemiamentioning
confidence: 99%
“…If the deterioration continues, atherosclerotic plaques rupture and can cause thrombosis, myocardial infarction, cerebral infarction, and other serious consequences. [177][178][179] Therefore, developing advanced techniques for early detection and theranostics of CVD-related changes such as atherosclerotic plaques and thrombosis are urgently needed. The pathological characteristics of CVD, such as low pH, high ROS levels, abnormal enzyme levels, lipid-rich necrotic core, extensive inflammatory cell infiltration, thin fibrous cap, and neovascularization, provide opportunities for developing nanodrugs with endogenous stimuli responsiveness/targetability for the diagnosis and treatment of CVD.…”
Section: Biomarker-responsive Nanotheranostics For Cardiovascular Dis...mentioning
confidence: 99%